Bishdag Area according to Written and Archeological Sources - Vitaly A. Babenko; Marina Ye. Kolesnikova (Oriental Studies)
Introduction. The article deals with the localization of Bishdag area mentioned in a number of written sources. Traditionally, the area is placed in Pyatigorye. The Turkic ‘Bishdag’ stands for ‘five mountains’, while there are a total of 17 laccoliths across the region. Goals. The study seeks to compare data from material, written and phonic sources pertaining to Bishdag area. Archeological evidence and available records make it possible to suggest it might be localized within the Mineral Waters Plain and the Kislovodsk Basin. Materials and methods. The work focuses on tangible, written and phonic (oral) data. The former are accidental finds and excavated materials from around the cities of Yessentuki, Kislovodsk, Pyatigorsk, and Novopavlovsk. Written sources include works by Arab (Ibn Battuta, Ibn Fadlallah al-Umari) and Persian (Nizam al-Din Shami, Sharaf al-Din Ali Yazdi, Abd al-Razzaq Samarqandi) writers, notes by the Russian Ambassador in Crimea, and accounts of modern authors (E. Çelebi, J. A. Güldenstädt, P. S. Pallas, J. Klaproth and A. Firkovich). Phonic data are contained in the works of E. Çelebi and A. Firkovich: these documented stories related to the fortress of Rim-Gora. The article also analyzes materials of Mongol toponymy from Yessentuki and its vicinities. The genetic, comparative historical and cartographic methods have proved most instrumental herein. Since the messages from written sources are scarce enough, they have been compared to the present-day landscapes and archeological evidence. The cartographic method is employed to localize Bishdag area and the place of celebrations described by Ibn Battuta. Results. In 1334, the Moroccan traveler Ibn Battuta visited Bishdag area. He described Ramadan celebrations in Özbeg Khan’s camp. It is necessary to distinguish between the place of the camp — and that of the celebrations. The latter may be localized near the Mashuk, Beshtau, Zheleznaya, Razvalka and Zmeika mounts, and next to mineral water springs. Conclusions. With due account of messages by Abd al-Razzaq Samarqandi, we suggest the borders of Bishdag area may lay within the Mineral Waters Plain and the Kislovodsk Basin. The territory hosts sites of different typology, which indicates that both nomadic and sedentary groups had inhabited the area.